Employers and higher education system - BondarenkoN. (Voprosy obrazovaniya / Educational Studies Moscow, 2013)
Based on the data obtained by Yuri Levada Analytical Center Natalya Bondarenko, senior researcher in the Living Standards Department of Levada Center, Moscow, Russian Federation. Email: nut@levada.ru Address: 17 Nikolskaya St., Moscow, 109012, Russian Federation. Using results of annual polls of employers from 2006 to 2012, the report presents an analysis of major labor market trends in hiring graduates from professional education institutions. The most recent poll was carried out in the second half of 2012 using panel sampling and involved 1,000 companies from six industries (manufacturing, construction, transport, communications, business services, and trade). It has been found out that the number of hired graduates of all levels of professional education reduced in 2012, as compared to 2011. The paper analyzes the demand for university graduates in the labor market as a whole and in each of the abovementioned industries. All categories of companies, either small, medium, or large, tend to employ higher education graduates less and less often. Intensity of using this recruiting channel is compared for all the three business sizes. The report analyzes how employers assess qualification of graduates from education institutions of different levels (universities, colleges, technical, vocational and trade schools). The report identifies the proportion of companies that have had an experience of hiring Bachelors and Masters, compares how company leaders assess qualification of double degree graduates and specialists, and specifies priority criteria for selecting candidates among HE institution graduates. The report has also examined intensity of cooperation between employers and the educational system, determining how this intensity depends on whether or not a company has an HR department. Major forms of such cooperation have been identified. Prospects for cooperation between businesses and professional educational institutions in 2012–2013 have been outlined.